2017
DOI: 10.1002/jbm.b.33921
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia effect and antibacterial efficacy of Fe3+/Co2+ co‐substitutions in β‐Ca3(PO4)2 for bone cancer and defect therapy

Abstract: The combined effect of cobalt and iron substitutions in β-Ca (PO ) as a potent material for application in hyperthermia and as a bone substitute is presented. Structural analysis reveals the preferential accommodation of Co and Fe at the Ca (5) sites of β-Ca (PO ) until the limit of ∼10 mol % and, thereafter, prefer Ca (4) lattice sites. Occupancy of both the Co and Fe ions induces a significant contraction of the β-Ca (PO ) unit cell. The Co /Fe co-substitutions in β-Ca (PO ) display magnetic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 62 publications
(226 reference statements)
0
10
0
Order By: Relevance
“…57 Another study also found that the accommodation of both Co 2þ and Fe 3þ in b-tricalcium phosphate could not only improve the hyperthermal effects, but also induce obvious antibacterial efficacy. 58 In addition, there is great potential for hydroxyapatite modified with Fe 3 O 4 for bone tumor treatment. 59 Collagen/hydroxyapatite with 1 or 2% magnetite content produced insufficient hyperthermia, while composite scaffolds with a magnetite content of 5% could act as regenerative scaffolds with hypothermic antitumoral effects.…”
Section: Magnetite (Fe 3 O 4 )-Based Materials For Bone Tumor Treatmentmentioning
confidence: 99%
“…57 Another study also found that the accommodation of both Co 2þ and Fe 3þ in b-tricalcium phosphate could not only improve the hyperthermal effects, but also induce obvious antibacterial efficacy. 58 In addition, there is great potential for hydroxyapatite modified with Fe 3 O 4 for bone tumor treatment. 59 Collagen/hydroxyapatite with 1 or 2% magnetite content produced insufficient hyperthermia, while composite scaffolds with a magnetite content of 5% could act as regenerative scaffolds with hypothermic antitumoral effects.…”
Section: Magnetite (Fe 3 O 4 )-Based Materials For Bone Tumor Treatmentmentioning
confidence: 99%
“…Ionic substitution in both α and βTCP is currently being investigated. A solid-state reaction, as well as the heat treatment of already precipitated powders, are commonly applied to synthesize these materials [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. It is worth underlining that there are two main directions in ionic modification of α and βTCP.…”
Section: Ionic Substitutions In Non-apatitic Calcium Phosphatesmentioning
confidence: 99%
“…It is not only magnesium that is being introduced into the βTCP crystal lattice. In the literature, following examples of other ionic modifications can be found: sodium [ 127 , 143 ], potassium [ 128 ], silver [ 135 ], manganese [ 132 ], silicon [ 111 , 133 ], strontium [ 107 , 112 , 113 , 114 ], copper [ 136 ], cobalt [ 137 ], aluminium [ 146 ], iron [ 139 , 140 , 141 ], lantanium [ 131 ], and rare earth elements [ 145 ].…”
Section: Ionic Substitutions In Non-apatitic Calcium Phosphatesmentioning
confidence: 99%
See 2 more Smart Citations